Respuesta :

Answer:

x = -⁷/9

Step-by-step explanation:

[tex] \frac{9x - 8}{3} = \frac{9x - 3}{2} [/tex]

Multiply both sides by 3

[tex] \frac{9x - 8}{3}*3 = \frac{9x - 3}{2}*3 [/tex]

[tex] 9x - 8 = \frac{3(9x - 3)}{2} [/tex]

Multiply both sides by 2

[tex] 2(9x - 8) = \frac{3(9x - 3)}{2}*2 [/tex]

[tex] 2(9x - 8) = 3(9x - 3) [/tex]

[tex] 18x - 16 = 27x - 9 [/tex]

Subtract 27 from each side

18x - 16 - 27x = 27x - 9 - 27x

-9x - 16 = -9

Add 16 to both sides

-9x - 16 + 16 = -9 + 16

-9x = 7

Divide both sides by -9

-9x/-9 = 7/-9

x = -⁷/9

ACCESS MORE